ANALISIS SKALA EKONOMIS PADA INDUSTRI JAJAN BEGINA DI DESA LUWUS KECAMATAN BATURITI KABUPATEN TABANAN - Komang Sonia Veronika; Ida Bagus Putu Purbadharmaja (NETIZEN: JOURNAL OF SOCIETY AND BUSSINESS, 2025)
This study aims to analyze the economic scale and the influence of capital, labor, and raw materials on production in the jajan Begina industry in Luwus Village, Baturiti Sub-district, Tabanan Regency. The jajan Begina industry is a household-based enterprise with significant potential to support the local economy and absorb labor, particularly during religious holidays in Bali. This research employs a quantitative method using the Cobb-Douglas multiple linear regression model. Primary data were collected through questionnaires distributed to 96 respondents using accidental sampling techniques. The variables examined in this study include capital, labor, raw materials, and production. The analysis was conducted to determine the simultaneous and partial effects of the independent variables on production, as well as to assess the industry’s economic scale. The findings reveal that capital, labor, and raw materials simultaneously have a significant effect on production. Partially, capital exerts the most dominant influence on production, with a regression coefficient of 0.561, followed by raw materials at 0.073, and labor at 0.028. The total regression coefficient value of 0.662 (>1) indicates that the jajan Begina industry in Luwus Village is operating under conditions of increasing returns to scale. This implies that an increase in input will lead to a more than proportional increase in output, reflecting a growing economy of scale in the industry.